Culex quinquefasciatus Late Trypsin Biosynthesis Is Translationally Regulated by Trypsin Modulating Oostatic Factor - Borovsky, Dov; Verhaert, Peter; Rougé, Pierre; Powell, Charles A.; De Loof, Arnold (Frontiers in Physiology, 2021)
Trypsin is a serine protease that is synthesized by the gut epithelial cells of female mosquitoes; it is the enzyme that digests the blood meal. To study its molecular regulation, Culex quinquefasciatus late trypsin was purified by diethylaminoethyl (DEAE), affinity, and C18 reverse-phase high performance liquid chromatography (HPLC) steps, and the N-terminal amino acid sequence was determined for molecular cloning. Five overlapping segments of the late trypsin cDNA were amplified by PCR, cloned, and the full sequence (855 bp) was characterized. Three-dimensional models of the pro-trypsin and activated trypsin were built and compared with other trypsin models. Trypsin modulating oostatic factor (TMOF) concentrations in the hemolymph were determined by ELISA and compared with trypsin activity in the gut after the blood meal. The results showed that there was an increase in TMOF concentrations circulating in the hemolymph which has correlated to the reduction of trypsin activity in the mosquito gut. Northern blot analysis of the trypsin transcripts after the blood meal indicated that trypsin activity also followed the increase and decrease of the trypsin transcript. Injections of different amounts of TMOF (0.025 to 50 μg) decreased the amounts of trypsin in the gut. However, Northern blot analysis showed that TMOF injections did not cause a decrease in trypsin transcript abundance, indicating that TMOF probably affected trypsin translation.